KAJIAN PENGGUNAAN PEMANIS SORBITOL SEBAGAI PENGGANTI SUKROSA TERHADAP KARAKTERISTIK FISIK DAN KIMIA BISKUIT BERBASIS TEPUNG JAGUNG (Zea mays) DAN TEPUNG KACANG MERAH (Phaseoulus vulgaris L.) - Aini, Fatiyan Yuwinda; Affandi, Dian Rachmawanti; Basito, Basito (Universitas Sebelas Maret (UNS), 2016)
The aimed of the study was to know the effect of the use of sorbitol in sensory characteristics, chemical characteristic, physical characteristics, and also caloric value of biscuits. The experiments was performed using a Completely Randomized Design (CRD) with one factor,that is subtitusion of sorbitol. There is three formulas: F1 (10% sorbitol); F2 (17% sorbitol); F3 (24% sorbitol). All three formulas were analyzed with preference test to get the best formula. Best formula was analyzed physical and chemical. The result of analysis was compared with control biscuits (sucrosa biscuits). The results of sensory analysis showed that was the most preferred biscuit is F3. Sorbitol biscuits had higher moisture content than the control biscuits. Caloric value of sorbitol biscuits lower than bicuits control. Subtitution of sorbitol on biscuits, could be decreased caloric value up to 2.6%. Spread ratio of sorbitol biscuits greater than the control biscuits. The colors of sorbitol biscuits brighter than bicuits control.